Pengaruh Penerapan Etika Bisnis dan Regulasi Hukum Ketenagakerjaan : Dampak Terhadap Kepuasan Kerja dan Citra Perusahaan - Resti; Halimah Azahrah; Arsyla Az-Zahra; Marshanda Muara Putri (INDO PUBLISHING, 2025)
The unilateral termination of employment (PHK) by local fashion company Erigo has sparked widespread public attention, particularly on social media. This case raises questions about the extent to which companies uphold business ethics and comply with labor laws. This study aims to understand termination practices from ethical and legal perspectives, and to analyze their impact on employee job satisfaction and corporate image. This qualitative case study focuses on the social phenomenon surrounding the Erigo PHK issue as seen on social media and online news. Data collection methods include document analysis and non-participant observation of posts by former employees and public reactions on platforms such as Twitter, Instagram, and news sites. A purposive sampling technique was used, involving key informants indirectly related to the case. In-depth interview participants were limited due to the study’s emphasis on public data. Thematic analysis and Miles & Huberman's interactive model were used for data analysis. Findings reveal that the termination process lacked transparency, ethical communication, and full legal compliance. This led to decreased job security among employees and a reputational crisis in digital public spaces. The study recommends integrating ethics, law, and open communication into human resource management, especially in employment crisis situations.